Analysis of Planning Carrying Out Investigation Skills Using the Next Generation Science Standards Learning Framework on Plant Structure and Function Material - Dien Aulia Bansu; Insih Wilujeng; Suyanta Suyanta (Postgraduate, University of Mataram, 2023)
Meaningful understanding becomes the goal of the learning process. Science as a scientific discipline not only includes theory but also practicum implementation as proof of the theory that has been taught. The implementation of practicum is a demand in the science learning process. Introducing and training students with practicum activities is still rarely done in schools in Gowa district. It is necessary to impose international educational standards that lead to more specific learning outcomes. The purpose of this study is to analyze planning and carrying out investigation skills using the NGSS-oriented inquiry learning model. This research is a qualitative descriptive research. The sample in this study was class VIII E students of SMP Negeri 4 Sungguminasa, Gowa, totaling 31 people. Sample determination is carried out by purposive sampling. The instrument used is in the form of a multiple-choice question test to determine the planning and carrying out investigation skills of students. Based on the results of the analysis, it can be seen that the planning and carrying out investigation skills of students are in the medium category with indicators determining the title to get the highest percentage, with 66.66% and the indicator of choosing tools and materials got the lowest percentage, which is 31.91% is in the low category on the material structure and function of plants